Briket Olahan Limbah Organik Sebagai Solusi Affordable Alternative Energy Dalam Upaya Mencapai Sustainable Development Goals 2030 - Muhammad, Rafa; Shaleh, Sultan Malikus; Usman, Sultan Syarief; Subagja, Sigit (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
The increase in people's lifestyles raises problems of energy and waste crises. The energy crisis occurred due to a rise in energy demand due to the 4.0 industrial revolution era. Meanwhile, waste problems arise as a result of public consumption. This study aimed to create a product formulation for biomass briquettes with organic waste as the primary raw material. This study used the Experimental Design Completely Randomized Design (CRD) method with four formulations. The first formulation (V1) with the composition of rice husk: dry leaves: sawdust: cardboard, respectively 10:6:0:4, V2 (10:6:4:0), V3 (10:6:2:2), and V4 (10:2:6:2) Briquette quality testing uses four assessment indicators, namely shrinkage, ash content, combustion rate, and flame initiation time. The results showed that the composition of V2 briquettes was the best formulation with a shrinkage value of 92.52%, ash content of 7.48%, combustion rate of 0.0049 g/s, and flame initiation time of 2m 48s. Based on the research results, the Briquette V2formulation can be an affordable alternative energy solution to overcome the energy crisis in the world.